Peningkatan Pengetahuan Keselamatan Kesehatan Kerja (K3) Dan Pengelolaan Limbah Padat di Home Industry Manufactur: Increasing Knowledge of Occupational Health and Safety and Solid Waste Management in Home Industry Manufacturing - azham umar abidin (ITB Journal Publisher, LPPM ITB, 2022)
Home industry workers in manufacturing have low to high occupational risks in their work environment. This community service activity aims to increase workers' knowledge of the hazards in the work environment and increase awareness of the use of personal protective equipment in the workplace. The activity was carried out using the grafting method, namely observation, education, and evaluation of the activity's stages. Based on the assessment results, this method is quite good in making workers master and understand basic knowledge in the field of occupational safety and health, as well as handling solid waste from daily industrial activities. Workers can apply the practice of using Personal Protective Equipment correctly and managing the waste generated. Increased knowledge of Occupational Safety & Health (OSH) and waste management in workers can reduce near misses, incidents or even minimize work accidents in the workplace.